2022
DOI: 10.1017/s0007114522000551
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of ultra-processed foods and IL-6 in two cohorts from high- and middle-income countries

Abstract: This study aimed to evaluate the association between ultra-processed foods (UPF) on serum interleukin-6 (IL-6), and to investigate the mediation role of adiposity. Participants were 524 adults from the EPITeen Cohort (Porto, Portugal) and 2888 participants from the 1982 Pelotas Birth Cohort (Pelotas, Brazil). Dietary intake was collected using food frequency questionnaires (FFQ) when participants were 21 years of age in the EPITeen and 23 years in the Pelotas Cohort. Serum IL-6 and body fat mass were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…Another limitation is the lack of information regarding other potential conditions than BMI that may link an unhealthy diet to periodontitis, such as the host immune response (Amar et al, 2007) or systemic inflammation. While one may speculate the validity of our findings, populational studies have identified an association between an unhealthy diet, characterized by high consumption of ultra‐processed food, and systemic inflammation, irrespective of body adiposity (Silva dos Santos et al, 2022), thus corroborating our results. Future studies, however, should further investigate other underlying conditions to clarify the mechanisms involved in this relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation is the lack of information regarding other potential conditions than BMI that may link an unhealthy diet to periodontitis, such as the host immune response (Amar et al, 2007) or systemic inflammation. While one may speculate the validity of our findings, populational studies have identified an association between an unhealthy diet, characterized by high consumption of ultra‐processed food, and systemic inflammation, irrespective of body adiposity (Silva dos Santos et al, 2022), thus corroborating our results. Future studies, however, should further investigate other underlying conditions to clarify the mechanisms involved in this relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding eating habits and serum markers, there were negative correlations between the consumption of fruits and vegetables and VEGF, and between processed meat intake and IL-10; besides, there were strong positive correlations between the consumption of processed meat and inflammation and aging markers (IL-6/IL-10, TNF-α/IL-10, and VEGF) before the physical distancing. In part, the present results resemble other studies, in that they highlight the importance of in natura foods consumption and diminished intake of ultra-processed foods to reduce inflammatory and aging-associated markers ( 63 66 , 91 , 92 ). A 6 months following the physical distancing, the aforementioned correlations were also lost, and a negative correlation between the consumption of processed meat and IFN-γ/IL-5 ratio arose.…”
Section: Discussionsupporting
confidence: 89%
“…Other biomarkers studied to a lesser extent are some proinflammatory cytokines such as IL-6. Dos Santos et al investigated the possible relationship between UPF consumption and IL-6 concentrations in two cohorts, showing an association only in women in the Portuguese cohort and only in men in the Brazilian cohort [ 57 ]. The conclusion was that the UPF intake could be associated with higher IL-6 levels, although the relation was not explained by adiposity [ 57 ].…”
Section: Upf and Low-grade Inflammationmentioning
confidence: 99%